2021
DOI: 10.1093/ehjdh/ztab101
|View full text |Cite
|
Sign up to set email alerts
|

Development of a machine learning model using electrocardiogram signals to improve acute pulmonary embolism screening

Abstract: Aims Clinical scoring systems for pulmonary embolism (PE) screening have low specificity and contribute to CT pulmonary angiogram (CTPA) overuse. We assessed whether deep learning models using an existing and routinely collected data modality, electrocardiogram (ECG) waveforms, can increase specificity for PE detection. Methods and Results We create a retrospective cohort of 21,183 patients at moderate- to high-suspicion of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(26 reference statements)
0
8
0
1
Order By: Relevance
“…Overall, 15 studies explored ML-based models to assist VTE diagnosis, either in the form of a pretest probability or to assist diagnosis after clinical presentation (Supplementary Table 4) [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] . Most of them do not describe clearly preprocessing steps, splitting/cross-validation, hyperparameters, and other performance metrics.…”
Section: Diagnosis Of Vtementioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 15 studies explored ML-based models to assist VTE diagnosis, either in the form of a pretest probability or to assist diagnosis after clinical presentation (Supplementary Table 4) [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] . Most of them do not describe clearly preprocessing steps, splitting/cross-validation, hyperparameters, and other performance metrics.…”
Section: Diagnosis Of Vtementioning
confidence: 99%
“…Overall, ML based prediction of VTE is limited so far, and current studies are sparse and problematic so further work is needed in that direction exploiting the advantage of big data. Somani et al 89 used an extensive source of data from the EHR, besides vital signs, lab and clinical data, deep learning-based embedding representation of ECG waveforms, as well as unstructured data from imaging reports. They also followed STROBE 94 and TRIPOD 67 guidelines for model development.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported similar advantages for a wide range of medical applications from radiology 17 to oncology 18 . For the task of PE detection, both Huang et al 19 and Somani et al 20 proposed a multimodal fusion model combining EHR data with CTPA and ECG respectively. Most previous work has focused on approaches using only one of several possible fusion strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Promising results for PE detection have been shown based on imaging data alone, and are further improved when combined with additional modalities. Both Huang et al 19 and Somani et al 20 proposed a multimodal fusion model combining EHR data with CTPA and ECG respectively for the detection task. When designing a multimodal fusion solution, several models can be considered: Multimodal vision-language models trained with a contrastive objective 21 , 22 have enabled zero-shot adaptation to novel tasks, without the need for fine-tuning.…”
Section: Introductionmentioning
confidence: 99%